Influential Article Review - The Profound Influence of Innovation on Design, Perception and Behavior - Carr, Jose; Ramsey, Marvin; Price, Ida (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation. We present insights from a highly influential paper. Here are the highlights from this paper: The innovation era has seen firms adopting a variety of organization designs with autonomous teams as their basic building blocks. Such organization designs have confronted firms with the challenge of managing complex task interdependence configurations. The predominant assumption within the organization design field for decades has been that task interdependence given by design would determine team behavior. We argue on theoretical grounds that research on interdependence should revisit the relationship between design and behavior. More specifically, we suggest social interdependence theory as a valuable complementary theoretical lens for examining the subtleties of how design shapes behavior and how behavior in turn may influence design. At the end of our discussion, we propose the implications for research and practice and present several research opportunities which are expected to further contribute to a better understanding of the strategic organization of innovation-led firms. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.